2015
DOI: 10.1016/j.ajog.2014.10.1093
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in hepatic diseases during pregnancy in the United States, 2002–2010

Abstract: OBJECTIVE While pregnancy-related severe liver disorders are rare, when they occur morbidity and mortality rates are increased for mothers and infants. The objective of this study was to examine the prevalence and trends of hepatic diseases during pregnancy hospitalizations from 2002 through 2010 in the United States. STUDY DESIGN Hospital discharge data were obtained from the Nationwide Inpatient Sample, the largest all-payer hospital inpatient care database in the United States that provides nationally rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 17 publications
2
25
0
3
Order By: Relevance
“…This referral bias (Berkson bias) has been identified previously for many conditions 28 . In addition, the lack of specific diagnosis codes for each of the LDoP conditions limits the accuracy of studies derived from administrative data 29 , which use the broad diagnosis code of “liver diseases of pregnancy” (ICD-9 code 646.7) and may include other hepatobiliary conditions which are not unique to pregnancy. Indeed, by manual review of their medical records, we excluded a large number of subjects with abnormal liver tests during pregnancy (47 out of 294), due to acute biliary conditions and chronic hepatitis which were captured under ICD-9 codes used for liver diseases unique to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…This referral bias (Berkson bias) has been identified previously for many conditions 28 . In addition, the lack of specific diagnosis codes for each of the LDoP conditions limits the accuracy of studies derived from administrative data 29 , which use the broad diagnosis code of “liver diseases of pregnancy” (ICD-9 code 646.7) and may include other hepatobiliary conditions which are not unique to pregnancy. Indeed, by manual review of their medical records, we excluded a large number of subjects with abnormal liver tests during pregnancy (47 out of 294), due to acute biliary conditions and chronic hepatitis which were captured under ICD-9 codes used for liver diseases unique to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…510 Whether the prevalence of these conditions has stabilized, decreased, or worsened since these reports is largely unknown. There is also a paucity of information on how the prevalence of chronic conditions varies by key socio-economic predictors of obstetric morbidity and mortality, including rural vs. urban residence, 11 income, 4,12 and insurance coverage status.…”
Section: Introductionmentioning
confidence: 99%
“…Injection drug use of opioids and heroin has increased in association with the prescription opioid epidemic as people have transitioned to injecting opioids and heroin after initiating prescription opioid use (Becker, Sullivan, Tetrault, Desai, & Fiellin, 2008; Grau et al, 2007; Muhuri, Gfroerer, & Davies), with concomitant increases in hepatitis C virus (HCV) infection (Suryaprasad et al, 2014). Two studies have estimated that between 10–17 of 100,000 pregnant women are chronically infected with HCV (Ellington, Flowers, Legardy-Williams, Jamieson, & Kourtis, 2015; Salihu et al, 2012). However, a recent retrospective study of inpatient pregnancies in the U.S. between 1998 and 2011, showed that HCV rates per 100,000 deliveries increased by over 5-fold, from 42 to 210 in those years, respectively (Salemi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%